English Communicative Needs Analysis for Tourist Guides on Untung Jawa Island - Yanti, Yanti; Manara, Christine; Ekarina, Ekarina; Engliana, Engliana (Cetta: Jurnal Ilmu Pendidikan, 2024)
Studies in English for Specific Purposes (ESP) often focus on researching English needs in the context of commercial tourist attraction areas. Little research has been done in addressing the English needs of community-based tourism (CBT). This study aims to investigate the English needs, specifically the English communicative skills of tourist guides on Untung Jawa island. The investigation is a mixed-method study. Data was collected using a survey questionnaire, interviews, and observation (job shadowing). Twenty-two (22) participants responded to the questionnaire and two tourist guides were interviewed. Job shadowing was also conducted with two tourist guides to record the communicative functions often used in their professional practice. Findings indicated that spoken English communicative function was not an immediate need for the tourist guides considering the little encounter with international tourists. There are some indications that written form of English may be needed in their tourist area. The results imply that the tourist guide needs scripted text that they can use in specific communicative events.